Sayyid Mawdudi's Contribution towards Islamic Revivalism in the Contemporary Islamic Political thought - Suleiman, Ibrahim; Gadau, Ya’u Idris (International Journal of Islamic Business & Management, 2018)
This paper discussed the role and ideas of Sheikh Mawdudi in religion and politics in India and later Pakistan, Lahore. It is very paramount that Islamic scholars are considered to be relevant in moulding the minds of Muslims Ummah towards adherence to their religion and participation in politics and electoral process. Therefore, this article highlights the major contributions made by Mawdudi and outlines his role in terms of revivalism during his life-time and beyond. This is accomplished by investigating his major works and his teachings especially in shaping participation in political circle so as to ensure that Muslims are participated in the political and electoral process in India and Pakistan. In his political thought, Sheikh Mawdudi believed strongly in the formation of Islamic state and participation of Muslims in politics and governance as against the other views of anti-democratic arguments. His major concern is to encourage Muslims Ummah to adhere to the teaching of Islam and participate in all government activities in order to protect the interest of their religion considering the diverse nature of these countries. Therefore, assessing the role played by Mawdudi will significantly improve our understanding of Islamization movement towards determining social reality, justice and equity along Islamic ethics and values.